2000
DOI: 10.1021/ac991008y
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Ultrafast Liquid Chromatography

Abstract: A novel liquid chromatographic system which enables high temperature ultrafast liquid chromatography (HTU-FLC) has been designed through the careful consideration of heat transfer, band broadening, and pressure drop. Studies of the effect of linear velocity on the HETP show that column efficiency at high velocity, especially of well-retained solutes, dramatically improves at higher temperatures. At 150 degrees C, at a flow rate of 15 mL/min with a 5 cm by 4.6 mm (i.d.) column packed with 3 microns polystyrene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 38 publications
2
141
0
2
Order By: Relevance
“…Increased column temperature increases the band broadening mechanisms due to longitudinal diffusion, and decreases the band broadening mechanisms due to increased mass transfer within the stationary phase and stagnant mobile phase. Alternatively, the more generally applied van Deemter equation has been used to study the effect of temperature on RPLC column efficiency by Yan et al [33]. The trends in the fitting coefficients for small molecules (A, B and C; see below) with temperature were more consistent with the van Deemter equation [34]:…”
Section: Influence Of Temperature On Column Efficiencymentioning
confidence: 89%
“…Increased column temperature increases the band broadening mechanisms due to longitudinal diffusion, and decreases the band broadening mechanisms due to increased mass transfer within the stationary phase and stagnant mobile phase. Alternatively, the more generally applied van Deemter equation has been used to study the effect of temperature on RPLC column efficiency by Yan et al [33]. The trends in the fitting coefficients for small molecules (A, B and C; see below) with temperature were more consistent with the van Deemter equation [34]:…”
Section: Influence Of Temperature On Column Efficiencymentioning
confidence: 89%
“…A viscosidade decresce exponencialmente em função da temperatura, 2,3 assim, o aumento da temperatura permite: a utilização de maiores vazões; o emprego de partículas com menores diâmetros; a utilização de colunas com maior comprimento ou conectadas em série.…”
Section: Influência Da Temperatura Sobre a Pressãounclassified
“…Um exemplo de como o aumento da temperatura permite o uso de maiores vazões é o trabalho de Yang et al 2 onde uma coluna ZirChrom-PS (50 x 4,6 mm, dp 2,5 μm) utilizada a 25 o C e com FM acetonitrila:água, 25:75 v/v, a uma vazão de 2 mL/min gera uma pressão de 400 bar, alcançando o limite máximo de pressão de um sistema convencional de cromatografia líquida de alta eficiência (High Performance Liquid Chromatography, HPLC). Quando a temperatura é elevada a 150 o C, a pressão é reduzida a 60 bar, permitindo o uso de uma vazão de 14 mL/min sem exceder o limite de pressão da bomba.…”
Section: Influência Da Temperatura Sobre a Pressãounclassified
“…Thus, SWC is potentially advantageous for high-speed separation. 20 However, few published studies to date have demonstrated high-speed separation using this method. [20][21][22][23] One of the major constraints on the development of SWC has been the poor stability of many stationary phases.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, few published studies to date have demonstrated high-speed separation using this method. [20][21][22][23] One of the major constraints on the development of SWC has been the poor stability of many stationary phases. The octadecylsilyl-silica gel (ODS) stationary phase, which is widely used in conventional RP-HPLC under ambient conditions, was A superheated water chromatography (SWC) method for the separation of alkyl esters of 4-hydroxybenzoic acid (parabens) using a zirconia-based stationary phase was developed and applied to real sample analysis.…”
Section: Introductionmentioning
confidence: 99%